Immediate Effectiveness of Planned Teaching on Knowledge and Practice Regarding Household Waste Management among the Rural Community People - Nilima Rakshale; Pratibha Wankhede; Charlotte Paul; Ashwini Gardhane; Sanjay Deshpande; Swarupa Chakole (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The generation of the waste and collection, processing, transport and disposal of waste -theprocess of ‘waste management’ - is important for both health’s of the public and aesthetic and environmentalreasons. The study uncontrolled hazards waste from the industry after mixing with municipal waste createpotential risk to human health. Objectives: 1. To assess the knowledge and practice regarding household wastemanagement among the rural community 2. To Assess Effectiveness of Planned Teaching on Knowledge andPractice Regarding Household Waste Management among the Rural Community People in Selected Area ofWardha District. 3. To correlate the study finding with demographic variable. Materials and Methods: Thisstudy was based on one group pre-test post-test experimental research study. The population was the ruralcommunity people from Sawangi and Salod in the Wardha district. The subject consisted of 50 communitypeople of 18-50 years of age in the selected rural community of Wardha district. Results: The minimumscore in the posttest was 13 and the maximum score was 18, the mean score for the posttest was 16.04±1.10with a mean percentage score of 89.11±6.14. The tabulated value for n=50-1 i.e. 49 degrees of freedom was2.00. The calculated ‘t’ value is much higher than the tabulated value at 5% level of significance for overallknowledge score of community people which is a statistically acceptable level of significance.